Political Objectives and Privatization Decisions - Selection of Firms into Privatization or Long-Term State Ownership in Romania - Ádám Szentpéteri; Álmos Telegdy (Hungarian Academy of Sciences, Institute of Economics, 2009)
With the help of a peculiar institutional feature of early Romanian privatization, when a group of firms was explicitly banned to become private, we test which factors contributed to the selection of firms into long-term state ownership. We find that politicians sheltered large and inefficient firms from privatization, which paid low wages and had high overdue payments. These results are consistent with minimization of employment losses, even if efficiency enhancement of privatization or revenue maximization had to be sacrificed. We hypothesize that this behavior was induced by the unfavorable economic conditions in Romania which brought about large employment losses during the first several years of economic transition.
Keywords: L33; P26; 330; privatization; government objectives; Romania; Privatisierung; Politisches Ziel; Öffentliches Unternehmen; Rumänien